Cuticular hydrocarbons as modulators of social interactions in honeybee colonies - Scholl, Jacob, author; Naug, Dhruba, advisor; Ode, Paul, committee member; Hoke, Kim, committee member (Colorado State University. Libraries, 2011)
Honeybees are known for their highly complex social organization with individuals of different ages working in a coordinated manner to ensure colony functionality. While local-level inter-individual interactions are critical in transferring global-level information about colony needs, these same interactions are also exploited by various pathogens to spread themselves within the colony. It is therefore important to understand the proximate mechanisms that generate the exact structure of the interaction network within the colony. While bees of different ages possess unique cuticular hydrocarbon (CHC) profiles providing a potential basis for mediating these interactions, it is not entirely clear whether these odor cues in fact play a role in organizing the interaction network among them. The first part of my thesis examines the CHC profiles of bees of different ages and how their neuronal sensitivity to these odors enable them to discriminate each other and generate the observed interaction network in the colony. Using behavioral observations to quantify the interaction frequencies between different age groups and using electroantennograms to determine the olfactory sensitivity of each age to the odor of every other age, I determined the correlation between the two. The results show that young bees are indiscriminant in their interactions, which matches their lack of olfactory bias toward any age-specific odor, while old bees interact mostly with bees of a similar age, which corresponds with their higher olfactory sensitivity to the odor of such bees. Age-based differences in both cuticular hydrocarbons and the olfactory sensitivity to them thus provide a mechanistic basis to the observed interaction structure in the colony and suggests that an active behavioral segregation is the primary mechanisms that generates the organizational immunity in the colony, shielding the younger bees from interacting with older bees who are also more likely to be infected with pathogens. The second part of my thesis examines if the energetic stress related to a pathogenic infection can alter the hydrocarbon profiles of individuals and lead to changes in the interaction network within the colony. Using gas chromatography, I was able to show that energetic state of an individual has a significant influence on its CHC profile. Following this, using a choice test where subjects at different energetic states were made to choose between chemical mimics of starved and satiated bees in a y-maze, I demonstrated that both fed and starved bees preferred to interact with recipients that are at similar energetic states. While this is somewhat surprising, a cost-benefit analysis showed how the decision to donate food is a function of both the energetic state of the receiver as well as the donor. While the benefit to cost ratio is positive for a depleted donor to donate to a starved recipient, this ratio is not positive for a fed donor to donate to the same starved recipient. This suggests that energetic stress, by changing the CHC profiles of individuals, can lead to social interactions being restricted between individuals of similar energetic states. Since the energetic state of an individual is likely to be correlated with its infection status, this has the potential to generate a behavioral segregation between uninfected and infected individuals and help maintain the organizational immunity of the colony. My thesis research therefore establishes the role of age- and condition-dependent olfactory cues in organizing the interaction network within the colony and its implications for disease dynamics.